Reviewing Sepa Language Extinction of the Indigenous Peoples of Amahai, Moluccas, Indonesia - Maggalatung, Muhammad; Ridwan, M.; Syarifudin, Syarifudin; Darma, Darma; Sulaeman, Sulaeman (Technium Social Sciences Journal, 2021)
Threat language can be found in various local languages in Indonesia, including the Sepa language of the Indigenous peoples of Amahai, Moluccas, where the nationalization of Indonesian is a threat to its extinction. This paper aims to look at the extinction of regional languages from the framework of modernization and contestation of regional languages with national languages. This study is conducted qualitatively, data collection based on interviews, literature study, and observation obtained from Raja Sepa, community leaders, customary stakeholders. Research shows that the language in Maluku is almost extinct in line with the narrowing of regional language spaces; the language has been abandoned by its speakers because of the process of modernization and migration. This study shows the need for revitalization of the Sepa language through facilitating the mapping of the Sepa language comprehensively, making the Sepa language dictionary, and integrating the Sepa language into the local curriculum.